Association between axial length and horizontal and vertical globe diameters - Jonas, Jost B.; Panda-Jonas, Songhomitra (Graefe's archive for clinical and experimental ophthalmology, 2017)
PurposeTo assess relationships between axial length and the horizontal and vertical globe diameters.Material and methodsThe study consisted of enucleated human eyes. The horizontal, vertical, and sagittal diameters were measured.ResultsThe study included 135 globes removed because of malignant uveal melanoma (111 globes) or end-stage painful glaucoma (n = 24 eyes). Mean axial, horizontal, and vertical diameters were 24.6 ± 2.6 mm (range: 20-35 mm), 23.7 ± 1.4 mm (range: 21-29 mm) and 23.7 ± 1.4 mm (range: 20-29 mm) respectively. The horizontal diameter and vertical diameter did not differ significantly (P = 0.92), while both were significantly (P < 0.001) shorter than the axial diameter. The horizontal diameter was significantly and linearly correlated with the vertical globe diameter (P < 0.001; regression line: vertical globe diameter = 0.84 × horizontal globe diameter + 3.69). The axial diameter was significantly (P < 0.001) associated with the horizontal diameter and vertical diameters in a bipartite manner. In eyes with an axial length ≤24 mm, horizontal and vertical diameters increased by 0.44 and 0.51 mm, respectively, for each mm increase in axial diameter, while in eyes with an axial length >24 mm, the horizontal and vertical globe diameter increased by a lower amount of 0.19 and 0.21 mm, respectively, for each mm increase in axial diameter.ConclusionsMyopic enlargement of the globe beyond an axial length of 24 mm takes place predominantly in the sagittal axis, leading to a change in the globe form from a sphere to an elongated form. It fits with the notion that myopic elongation may occur by an elongation of the eye walls in regions close to the globe’s equator.